The Effect of Lasers on the Healing of Periapical Lesion: A Systematic Review: Lasers and periapical lesion healing - Hazrati, Parham; Azadi, Ali; Tizno, Ashkan; Asnaashari, Mohammad (Journal of Lasers in Medical Sciences, 2024)
Introduction: Endodontic treatment of teeth with periapical lesions presents more clinical difficulty. Various lasers in several methods are used in endodontics, and most of them are utilized as an adjunctive protocol in order to reduce the bacterial load of the root canal system. Improved disinfection plays a crucial role in enhanced and accelerated healing of periapical lesions. This review aims to summarize studies assessing the effect of lasers on periapical lesion healing. Methods: PubMed/MEDLINE, Scopus, Embase, and Web of Science (ISI) online databases were searched, with no publication year or status restriction, for relevant articles on April 2023. Clinical studies evaluating the effect of laser application on the periapical lesion of patients using radiographic assessment were considered eligible for inclusion. Results: Eight studies were included after carefully screening the obtained articles, first by their title and abstract and then by their full texts. Diode (4), Er, Cr: YSGG (3), and Nd: YAG (1) lasers were used with output powers that varied from 0.75 to 2 watts. Photodynamic therapy was employed in two studies, and in other studies, the root canal system was directly irradiated. Irradiation of the root canal system was adjunctive to standard preparation in all studies. The healing of the teeth treated with lasers was not inferior to those conventionally treated. In all of the included studies, laser application outperformed the standard cleaning and shaping protocol; however, this improved or faster healing was not statistically significant in most studies. Conclusion: Lasers might expedite and improve the healing process of periapical lesions. Since lasers enhance the quality of cleaning of the root canal system, it is hard to point out the exact mechanism of it. Further investigations are needed to realize the effectiveness of this treatment modality and to discover the underlying biological concepts.